KARAKTERISTIK EKSTRAK KULIT BUAH MANGGIS (Garcinia mangostana L.) DAN BUNGA ROSELLA (Hibiscus sabdariffa Linn) SEBAGAI BAHAN PANGAN FUNGSIONAL PADA VARIASI JENIS PELARUT DAN SUHU EKSTRAKSI - Kartana, I Made; Wrasiati, Luh Putu; Putra, Gusti Putu Ganda (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2023)
Mangosteen pericarp and rosella flower can be used as a functional food. The aims of this study were to determine the effect of solvent type and extraction temperature on the characteristics of the powder extract of mangosteen pericarp and rosella flower, determine the type of solvent and extraction temperature that can produce the best characteristics of the powder extract of mangosteen pericarp and rosella flower, and to know the compounds which contain on the characteristics of the powder extract of mangosteen pericarp and rosella flower. The experiments were a factorial experiment with two factors which were designed with a randomized block design. The first factor is the type of solvent which consists of ethanol 96%, acetic acid, ethanol 96%:acetic acid (1:1), ethanol 96%:asam asetat (2:1). Second factor is extraction temperature which consists of room temperature, the temperature of 40 ± 2 o C, 50 ± 2 o C, 60 ± 2 o C with maceration time is 2 hours. The results showed that the solvent of ethanol 96% 1:1 acetic acid at room temperature and the interactions have a significant effect on the yield, total phenol, and antioxidant capacity. In the analysis of total anthocyanin only the solvent type and the extraction temperature had a significant effect, meanwhile, both interactions didn’t affect anything. Ethanol 96% 1:1 acetic acid at room temperature produced the best characteristics of the powder extract of mangosteen pericarp and rosella flower with yield characteristic 20,32±0,26 a %, total phenol 9,5903±0,05 mg GAE/100g, antioxidant capacity 47,6796±1,49 mg GAE/100g, dan total anthocyanin 11,10 %. Meanwhile, the types of chemical compounds analyzed with the GC-MS method on the powder extract of mangosteen pericarp and rosella flower are metiletilasetat , dihidropiran , karbonilklorida , 2- propanal , 2-furanon , tetrahidrotiazol , lakton , pentadesil ester .